Hydrodynamic Cavitation: A Promising Technology for Industrial-Scale Synthesis of Nanomaterials - Sun, Xun; Chen, Songying; Liu, Jingting; Zhao, Shan; Yoon, Joon Yong (Frontiers in Chemistry, 2020)
One of the most challenging issues for the large-scale application of nanomaterials, especially nanocarbons, is the lack of industrial synthetic methods. Sonochemistry, which creates an extreme condition of high pressure and temperature, has been thereby applied for synthesizing a wide variety of unusual nanostructured materials. Hydrodynamic cavitation (HC), characterized by high effectiveness, good scalability, and synergistic effect with other physical and chemical methods, has emerged as the promising sonochemistry technology for industrial-scale applications. Recently, it was reported that HC can not only significantly enhance the performance of biochar, but also preserve or improve the respective chemical composition. Moreover, the economical efficiency was found to be as least one order of magnitude higher than that of conventional methods. Due to the great potential of HC in the industrial-scale synthesis of nanomaterials, the present perspective focuses on the mechanism of sonochemistry, advances in HC applications, and development of hydrodynamic cavitation reactors, which is supposed to contribute to the fundamental understanding of this novel technology.